Cardiac myxoma - 2 years experience at a tertiary care center - K., Geetha; M., Vani; Kachappilly, Jeena Sam; George, Pretty Zachariah (International Journal of Research in Medical Sciences, 2017)
Background: Cardiac myxomas are the most common primary neoplasms of the heart. The current study aims to ascertain the clinical relevance of histomorphological classification and to postulate the possible cell of origin of cardiac myxomas. Methods: A total of 7 cases were analysed and reviewed with the assessment of the clinical presentations and gross and microscopic pathology along with immunohistochemical findings. All these patients were followed up to look for recurrence. Results: Of the total cases there were 5 women and 2 men. The mean age at presentation was 49 years. The most common presenting complaint was dyspnoea. On microscopy all the cases had a myxoid stroma with cells arranged in a predominantly single stellate cell pattern subtype. The tumor cells in all the cases were diffusely and strongly positive for vimentin with variable expression of S 100, CD 34, CD 68 and desmin. Conclusions: The identification of histological variability of cardiac myxoma has no significant clinical impact. Our study confirms the postulation that myxomas develop from multipotent mesenchymal stem cells.